2011
DOI: 10.1105/tpc.110.080770
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisABERRANT PEROXISOME MORPHOLOGY9 Is a Peroxin That Recruits the PEX1-PEX6 Complex to Peroxisomes

Abstract: Peroxisomes have pivotal roles in several metabolic processes, such as the detoxification of H 2 O 2 and b-oxidation of fatty acids, and their functions are tightly regulated by multiple factors involved in peroxisome biogenesis, including protein transport. This study describes the isolation of an embryonic lethal Arabidopsis thaliana mutant, aberrant peroxisome morphology9 (apem9), which is compromised in protein transport into peroxisomes. The APEM9 gene was found to encode an unknown protein. Compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
119
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 73 publications
7
119
0
Order By: Relevance
“…Arabidopsis RNAi lines targeting PEX1, PEX6, or PEX26 display decreased b-oxidation and matrix protein import (Nito et al, 2007;Goto et al, 2011). Although PEX1 is the most commonly mutated gene in peroxisome biogenesis disorder patients (for review, see Braverman et al, 2016), Arabidopsis pex1 mutants were only recently reported (Rinaldi et al, 2017).…”
Section: Atp-dependent Receptor Retrotranslocationmentioning
confidence: 99%
See 4 more Smart Citations
“…Arabidopsis RNAi lines targeting PEX1, PEX6, or PEX26 display decreased b-oxidation and matrix protein import (Nito et al, 2007;Goto et al, 2011). Although PEX1 is the most commonly mutated gene in peroxisome biogenesis disorder patients (for review, see Braverman et al, 2016), Arabidopsis pex1 mutants were only recently reported (Rinaldi et al, 2017).…”
Section: Atp-dependent Receptor Retrotranslocationmentioning
confidence: 99%
“…The viable aberrant peroxisome morphology9 missense allele shows wild-type b-oxidation but impaired matrix protein import in some cells (Goto et al, 2011). The pex26-1 splice-site mutation confers b-oxidation deficiency and low PEX5 levels like typical pex6 mutants .…”
Section: Atp-dependent Receptor Retrotranslocationmentioning
confidence: 99%
See 3 more Smart Citations